Macroeconomic determinants of stock market returns: Evidence from Oman - Shehab, Ayman Al (Asian Economic and Financial Review, 2023)
This paper aims to analyze the long- and short-term effects of macroeconomic factors on stock market returns in the Sultanate of Oman, particularly the effects of inflation (CPI), interest rates (IR), foreign exchange reserve (FER), money supply (M2), per capita gross domestic product (GDP), trading balance (TB), and oil prices (OP) on the returns of the main index of the Muscat Stock Exchange (MSX30). Additionally, the paper aims to examine whether the effects changed after the low oil price crisis at the end of 2014. The autoregressive distributed lag (ARDL) model was employed to analyze quarterly data for the full sample period (2009 Q2–2022 Q4), and for the oil price crisis period (2014 Q4–2022 Q4). The findings indicate that FER and per capita GDP had positive long-term effects on the returns of the MSX30, while M2 had a negative effect. It was also found that FER and OP had a negative effect in the short run, and the short-term impact of IR and TB were positive. Moreover, the findings during the oil price crisis indicate that the M2 continued to have a negative long-term impact, while in the short run, FER had a positive impact and TB had a negative impact.